Próba określenia sposobu oceny dopuszczalności prognoz wyznaczanych metodą najmniejszego sympleksu - Szanduła, Jacek (The trial of establishing the way of forecasts acceptance evaluation for forecasts built by the smallest simplex method, 2007)
The paper considers the theme of time series forecasting using the smallest simplex method proposed in 1990 by G. Sugihara and R.M. May. The idea o f the method is described. There is conducted a trial of establishing the way of forecasts acceptance evaluation in the paper. Because of the lack of checking possibilities of forecasts error variances, alternative approach is regarded. There is set an introductory hypothesis of possibilities benefit from others ways of forecasts acceptance evaluation. Among ways taken into account are: dimensional simplex measure, distances between simplex vertices and its gravity center, weighted differences between coefficients of simplex vertices and its gravity center, variance of coefficients generating forecast, theoretical variable consisted of above measures. The author proposes and presents in practice the procedure of verifying possibilities of use of considered ways of forecasts acceptance evaluation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 224-233